Skrining Aktivitas Antibakteri Ekstrak Etanol 70% Dari Beberapa Daun Tanaman Di Indonesia Terhadap Bakteri Staphylococcus aureus Serta Bioautografinya - Rahmawati, Ida, Rima Munawaroh, M.Sc., Apt (2016)
Bacteria is considered as one of the cause of infection. One kind of bacteria that cause infection is Staphylococcus aureus bacteria. Some plants have antibacterial activity such as sembukan, tamarind, gandola or binahong, spider lily, marigolds, guava, fragrant pandan, beluntas, patchouli, and Moringa. The purpose of this study was to determine the antibacterial activity on Staphylococcus aureus of 70% ethanol extract of ten leaves of plants with the highest activity, and the compound which play role for the antibacterial activity. The maceration method was selected as the method in producing solvent extract by using ethanol 70%. The antibacterial activity test was conducted by using a solid diffusion (Kirby Bauer). 20% concentration extract was absorbed on blank disks as much as 15 mL/ disc which then placed on the media Agar Muller Hinton inoculated with bacteria. Positive control used for chloramphenicol antibiotic and DMSO as a negative control. The bioautografi was performed by the method of bioautografi contact. Results obtained from the antibacterial activity test indicated that guava leaf extract has the highest inhibition zone at 12.5 ± 1 mm compared to other extracts. Thin Layer Chromatography (TLC) was performed by using silica gel stationary phase GF254 and mobile phase BAW (4:1:5 v/v/v upper phase). The TLC test was performed by using a stationary phase of silica gel GF254 and mobile phase BAW (4: 1: 5 v/v/v upper phase). The result of TLC and phytochemical screening test indicated any flavonoids, tannins, saponins, and terpenoids. The results of bioautografi indicated that the compounds which play role for the antibacterial activity is a compound of saponin.